Financial Management of Islamic Boarding Schools from the Perspective of Agency Theory: Case Study of Modern and Traditional Islamic Boarding Schools in Pekanbaru City - Abdullah, Eramli Jantan; Ilyas, Ilyas; Zaitun, Zaitun (Scidac Plus, 2026)
This study aims to examine financial management practices in Islamic boarding schools (pesantren) from the perspective of Agency Theory. The main problem addressed is the persistence of challenges related to transparency, digitalization, and human resource capacity in sharia-based financial management within non-profit Islamic educational institutions. A qualitative multiple-case study design was employed, focusing on two pesantren in Pekanbaru, Indonesia: Babussalam and Dar El Hikmah. Data were collected through in-depth interviews, observations, and document analysis involving school leaders, foundation administrators, and financial managers. The findings reveal that both institutions have implemented basic financial management mechanisms, including planning, execution, and supervision. However, significant challenges remain in terms of transparency, adoption of digital systems, and professional competence. From an Agency Theory perspective, the relationship between school leaders (principals) and financial managers (agents) indicates potential information asymmetry and centralized decision-making, particularly in strategic financial allocation. Dar El Hikmah demonstrates more structured governance and partial adoption of digital accounting systems, whereas Babussalam relies on manual recording practices. Both institutions also face limitations in external auditing and stakeholder engagement in financial reporting. This study contributes to the application of Agency Theory in Islamic non-profit education by highlighting the interaction between moral-religious values and governance structures in mitigating agency problems. Practically, it recommends digital financial systems, regular external audits, formalized internal regulations, and enhanced professional training in Islamic accounting to strengthen accountability and long-term sustainability.